Makna Generasi Sandwich Pada Film Cinta Pertama, Kedua, dan Ketiga (Analisis Semiotika Charles Sanders Peirce) - Putri, Paramitha Amelia; Prasetio, Arie (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Indonesia is facing the phenomenon of the sandwich generation, which plays a dual role in the financial affairs of three generations at once. Data from the March 2022 National Socio-Economic Survey shows that 8.4 million Indonesians (62.71%) belong to the sandwich generation. The movie "First, Second, and Third Love" reflects this reality, directed by Gina S. Noer based on a true story. This study applies Charles Sanders Peirce's Semiotic method to analyze triadic signs. The research shows that individuals give meaning to societal experiences by using the Social Reality Construction Theory. The movie becomes a representation of social reality, helping to understand the complexity of the sandwich generation's life in the context of Indonesian families. To break the chain of the sandwich generation that can damage the next generation, priority awareness, implementation of life limit setting, role as an entrepreneur, and increased educational awareness are needed to change the toxic culture.